Critical levels of phosphorus in the soil for forage legumes, inoculated with arbuscular mycorrhizal fungi. Technical Note - González, P. J.; Ramírez, J. F.; Rivera, R.; Crespo Flores, G. (Cuban Journal of Agricultural Science, 2016)
The effect of arbuscular mycorrhizal inoculation on critical levels of phosphorus in the soil for Neonotonia wightii and Stylosanthes guianensis was evaluated. An amount of 20 places were selected, with concentrations of assimilable phosphorus from 0 to 20 cm, which varied from 9 to 55 mg kg-1. In each place, the response of both legumes to phosphoric fertilization was evaluated with or without inoculation of the arbuscular mycorrhizal fungi Glomus cubense. Using the method of Cate and Nelson, critical levels of phosphorus in the soil were obtained for these legumes, inoculated or not. For N. wightti without inoculation, the critical level was 35 mg kg-1(R2=0.90), but with the inoculation with G. cubense, it decreased up to 20 mg kg-1 (R2=0.87). For S. guianensis, without inoculation, the result was 20 mg kg-1 (R2=0.83). In presence of G. cubense, there was no response to phosphoric fertilization. Key words: soils, nutrition, phosphoric fertilization, Neonotonia wightii, Stylosanthes guianensis.